Separatisme dalam Perspektif Sejarah - Djoko Suryo (Unisia, 2003)
Separatism denotes one of the historical phenomenon that emerges since human society know the form of the building of political lifecommunity either in the form of the village federation association, the kingdom or modern state from past time up to now. The phenomena of separatism truthfully there was in the era of old kingdom, for instances, the elaslccal Egypt, Mesopotamia, Greek, and Roman Empire, and the kingdom of Indonesia, for examples, Sriwijaya Majapahit, Demak, Pajang and Mataram. Ideology and the spirit of nationalism and the globalization participate In movitating the separatism in Indonesia either positively ornegatively. The phenomenon of separatism mentionedabove needs to be solved by approaching and political policies and the strongest great de sires from Indonesian people themselves to resist the unity of nation and state of Indonesia.